Developing a sustainable community forest-based village ecotourism in Oro-Oro Ombo, Malang: What is the effect of Batu’s West Ring Road? - Wirahayu, Yuswanti Ariyani (2022)
The development of village tourism based on local potential is increasingly important for economic improvement and community welfare in sustainable development. The objectives of this study were: (1) to analyze the development of a sustainable community-based forest of Oro-Oro Ombo Ecotourism Village; (2); to analyze the effect of the construction of the West Ring Road of Batu City on the development of ecotourism in Oro-Oro Ombo Village; and (3) to examine the problems and challenges in managing sustainable ecotourism in Oro-Oro Ombo Village. This study was quantitative descriptive. Data involved primary data and secondary data. Primary data were collected through observations and interviews. Secondary data were collected from related agencies such as the Central Statistics Agency and the Tourism Office. Data were analyzed using a scoring and single tabulation method and SWOT analysis. The SWOT analysis results showed that Oro-Oro Ombo Tourism Village had the potential to grow well as a tourist destination. Oro-Oro Ombo Village was very underdeveloped compared to other areas in Batu. However, it started to grow rapidly, including its tourism sector after the West Ring Road of Batu City was built in 2018. Findings confirmed that cooperation between the State Forest Company (Perhutani), the community, and investors as the Oro-Oro Ombo Tourism Village developer went very well in developing tourism. The challenge is to maintain the sustainability of the forest and the waterfalls (Coban Rais, Coban Putri, and Coban Kaca) in the forests on the slopes of Mount Panderman. Oro-Oro Ombo Tourism Village is in the stable growth strategy stage according to the IFAS and EFAS quadrants, so sustainable tourism development according to the SDG’s (UNWTO) criteria needs to be pursued.